Differences in physical literacy levels of students at SMP Plus Al-Musthafa based on gender and parental education level - Maulana, Rizal Ahmad; Wibowo, Yuyun Ari; Priambadha, Aprida Agung; Ries, Francis (Jurnal Pendidikan Jasmani Indonesia, 2025)
The study aimed to identify differences in the physical literacy levels of SMP Plus Al-Musthafa students based on gender and their parents’ educational levels. A quantitative approach was utilized with a cross-sectional survey design. A total of 143 students from SMP Plus Al-Musthafa participated in the study, selected through purposive sampling method. Data were collected using the Adolescent Physical Literacy Questionnaire (APLQ) and analyzed using descriptive statistics and the Independent Samples t-Test. The results indicated significant differences in physical literacy levels based on gender (p = 0.002) and the father’s education level (p = 0.014), with higher scores observed in male students and those whose fathers were educated at the diploma level or higher. No significant differences were found based on the mother’s education level (p = 0.210). These findings suggested that gender and the father’s education level played a role in differentiating the physical literacy levels of adolescents. Contextually, these results are important for the development of physical literacy in Indonesia, which still faces challenges with physical activity disparities between genders. The practical implication is that physical education learning needs to be more gender-responsive and encourage parental involvement in fostering an active lifestyle for children.